The writing stick, precious wood tree -a new Mexican species of Dalbergia (Leguminosae, Papilionoideae) - Rzedowski, Jerzy; Guridi-Gómez, Lydia I. (Instituto de Ecología, A.C., 1988)
Dalbergia palo-escrito sp. n., is described from the montane mesophyllous forest of the Sierra Madre Oriental in the state of Hidalgo and in adyacent parts of San Luis Potosí and Querétaro. It seems to be related to D. tucurensis Donn. Smith, known from Belize and Chiapas to Nicaragua. An anatomical description of the wood is provided.